Where are the Rent Seekers? - Arye L. Hillman; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2016)
In a remarkably simple and yet in one of the most original and insightful observations of 20th century economics, Gordon Tullock observed that there are efficiency losses when public policies and political behavior create contestable rents. Tullock also observed that social losses from contesting rents appeared smaller than might be expected. The question is then raised `where are the rent seekers?' Tullock proposed that rent seeking was restrained by political accountability and `free-riding' incentives in interest groups. We affirm Tullock's explanations, which can be extended to locate rent seekers under different political institutions. We compare Tullock with Gary Becker, who focused on deadweight losses from redistribution and concluded, in contrast to Tullock, that political redistribution is efficient. The comparison highlights the significance of the recognition of rent seeking. By excluding rent-seeking losses from the social costs of redistribution, Becker could arrive at a conclusion more favorable than Tullock to an ideology that sees merit in extensive redistribution.
Keywords: H11; 330; rent seeking; rent creation; deadweight losses; income distribution; interest groups; contest models; Gordon Tullock; Gary Becker; Donald Wittman